Prognostic value of neutrophil-to-lymphocyte ratio and fibrinogen levels in ovarian cancer (Medical Journal of Indonesia, 2023)
BACKGROUND High neutrophil-to-lymphocyte ratio (NLR) and fibrinogen levels have been associated with mortality in several malignancies. However, the studies on the association between NLR or fibrinogen levels and ovarian cancer prognosis are inconsistent. This study aimed to investigate the prognostic roles of NLR and fibrinogen in ovarian cancer. METHODS A systematic search of electronic databases was performed to analyze studies on the association of pre-treatment NLR and fibrinogen levels with overall survival (OS) and progression-free survival (PFS) among patients with ovarian cancer. The hazard ratio (HR) and corresponding 95% confidence intervals [CIs] were analyzed. All statistical analyses were done using RevMan version 5.4 (Cochrane, United Kingdom). RESULTS A total of 7,312 patients from 27 studies were included. The median cut-off for high NLR was 3.6 for OS among 17 studies and 3.23 for PFS among 11 studies reporting an NLR HR. The median cut-off for fibrinogen levels was 4.0 in 9 studies reporting fibrinogen levels HR. High NLR was associated with lower OS (HR 1.35, 95% CI 1.18 to 1.55, p<0.0001, I2 = 76%) and PFS (HR 1.35, 95% CI 1.14 to 1.60, p = 0.0005, I2 = 71%). High fibrinogen levels were associated with lower OS (HR 1.44, 95% CI 1.14 to 1.82, p = 0.002, I2 = 81%) and PFS (HR 1.34, 95% CI 1.17 to 1.55, p<0.0001, I2 = 15%). This association occurred in all ovarian cancer types. CONCLUSIONS High pre-treatment NLR and plasma fibrinogen levels were related to poor OS and PFS in ovarian cancer.